(untitled) (Bangladesh Journal of Plant Breeding and Genetics, 2016)
Combining ability for yield and yield components were carried out in a 8×8 diallel cross of white grain quality protein maize (QPM) to determine the general combining ability (GCA) of the parents and specific combining ability (SCA) of the crosses. Significant mean sum of squares due to GCA and SCA were observed for all the characters studied. Higher magnitude of SCA variance than GCA variance clearly indicated the predominance of non-additive gene action for all the traits. The parental lines P4, P7 and Q6 were found to be the best general combiner for yield components and these parents could be used as donor parents in hybridization to improve traits like days to tasseling, days to silking, plant height, ear height, ear length, ear diameter, grains per ear and 1000 grain weight by accumulation of favorable genes. The significant positive SCA along with high mean yield, the crosses Q5 × P7, P7× Q6 and P7× Q2 could be used for commercial variety development, after verifying their performance over locations.